تقييم إدارة المخلفات الطبية بالمراكز الصحية بمدينة سرت المركز من وجهة نظر الطواقم الطبية والطبية المساعدة - الزرقة , علي عمران; فرج, فجرة صالح (Scientific Journal of University of Benghazi, 2023)
This study aims to assess the management of medical waste in health centers in the city of Sirte, the center. And the medical assistants in the health centers (Al-Zafaran Health Center, Omar Al-Mukhtar Health Center, and the Third Residential District Health Center), which numbered (30) forms, then a description of the study community and the study sample was presented, and statistical analysis was relied on using the statistical program (spss) statistical package for social science to test hypotheses, using statistical methods (arithmetic mean and standard deviation in data analysis and hypothesis testing). The study was conducted during the months of March and April of this year. The study concluded with a number of results, the most important of which are: the lack of proper management of medical waste within the health centers, and the process of separation and disposal of medical waste is not well done, and in light of these results, the study recommended the necessity of organizing a number of seminars and lectures on the proper management of dealing with waste medical.